Field test to evaluate colostrum quality in alpaca - Flodr, Hanna (2012)
In the majority of livestock species, the concentration of maternal immunoglobulin (Ig) in colostrum determines the Ig level in their offspring, and the failure of passive transfer of maternal immunoglobulins results in their susceptibility to disease. This study evaluates two methods (visual assessment and Brix refratometry) for determining alpaca colostrum quality in the field. Evaluations of 26 fresh colostrum samples from 77 alpaca mothers were compared with the results obtained by radial immunodiffusion assay for 77 blood serum samples from 36-48 hours old offspring, and 26 colostrum samples. The colostrum was collected from the dams immediately postpartum and pre-suckling and blood was taken from the crias by jugular venipuncture. Grades of calostral viscosity were assessed visually, with 60% at 2-5, and total calostral solids measured by Brix sugar refractometry averaged 37.3%. The radial immunodiffusion test yielded newborn IgG serum levels of 2679 ± 603.4 mg/dL and colostral IgG levels of 28337± 5593 mg/dL, and only one animal registered failure of immune transfer with serum levels of 750 mg/dL. Results obtained by visual assessment of the colostrum coincide with those obtained by refractometry (p=0.0007), but differ from the serum IgG concentrations in the newborn animals (p=0.15), as do the Brix refractometry readings (p=0.338). Due to the lack of low IgG levels in the colostrum samples, it was impossible to determine if a relationship exists between observed viscosity and colostral IgG concentration. Nonetheless, the positive correlation (p<0.001) between viscosity and Brix refractometry readings point to the need for further research.